Impairment in global protein synthesis uncouples UPR gene induction from HAC1 mRNA splicing in Saccharomyces cerevisiae - Geronimo, Ralph Allen Capistrano; Ishiwata-Kimata, Yuki; Funahashi, Yutaka; Izawa, Shingo; Kimata, Yukio (Frontiers in Microbiology, 2025)
Upon dysfunction of the endoplasmic reticulum (ER), also known as ER stress, eukaryotic cells alter their transcriptomes. This cytoprotective response is called the unfolded protein response (UPR), which is mediated by Ire1 and HAC1 in the yeast Saccharomyces cerevisiae. ER stress induces self-association and activation of the ER-resident transmembrane endoribonuclease Ire1, which catalyzes the splicing of HAC1 mRNA. It is widely accepted that HAC1 mRNA is translated into the nuclear transcription factor Hac1, only after being spliced. To investigate the cellular response to ethanol-induced ER stress, here we gradually added ethanol into S. cerevisiae cultures until reaching a final concentration of 16%. Unlike conventional ER stressors, such as tunicamycin and dithiothreitol (DTT), the ethanol exposure did not elicit the Ire1- and HAC1-dependent UPR gene induction, even though Ire1 was activated and HAC1-mRNA was efficiently spliced. Under the ethanol stress condition, global protein synthesis was nearly abolished, and the Hac1 protein level remained low, despite the presence of spliced HAC1 mRNA. Furthermore, treatment with the translation inhibitor cycloheximide abolished DTT-induced UPR gene induction. As the UPR signaling pathway requires translation of the spliced HAC1 mRNA, integrity of the translation machinery is deduced to be essential for UPR gene induction. In summary, we demonstrated that impairment of the translation machinery can actually block UPR gene induction under certain stress conditions. We also propose that this represents an advantageous regulatory system that prevents unnecessary gene induction.